Impact of Pregnancy on Maternal Cardiac Atria - Martin, Robert B.; Nelson, David B.; Stewart, Robert; Matulevicius, Susan; McIntire, Donald D.; Cunningham, F. Gary (American Journal of Perinatology, 2017)
Objective The aim of this study was to assess atrial changes across pregnancy and postpartum using cardiac magnetic resonance imaging (cMRI) to measure atrial end-diastolic volume (EDV).Study Design This was a 2-year prospective observational study of healthy nulliparous women. Each underwent serial cMRI in both maternal left lateral and supine positions at five epochs: 12 to 16 weeks, 26 to 30 weeks, 32 to 36 weeks, within 48 hours after delivery, and 12 weeks postpartum. EDV was calculated and compared with 12-week postpartum values.Results A total of 24 women completed the study. One woman developed preeclampsia, and her data were excluded. Mean age was 27 ± 2.8 years, and mean body mass index was 25.4 ± 3.8 kg/m2. Left atrial EDV increased by 12 weeks (p = 0.045) and remained significantly elevated through 32 to 36 (p < 0.0001) weeks. Maternal lateral positioning was associated with larger left atrial EDV after 12 weeks. Right atrial EDV was significantly elevated at 26 to 30 (p = 0.04) and 32 to 36 (p = 0.02) weeks in the lateral position, though there was no difference in the supine position.Conclusion We documented a significant increase in EDV for both atria during pregnancy. Volume changes were greater in the lateral compared with the supine position, with the most dramatic changes in left atrium at 32 to 36 weeks.
Keywords: atria; cardiac remodeling; cardiac magnetic resonance imaging; end-diastolic volume